MENINGKATKAN KINERJA GURU DALAM PROSES PEMBELAJARAN DI KELAS MELALUI SUPERVISI EDUKATIF KOLABORATIF DI SEKOLAH DASAR - Tuti Aina (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
This research is motivated due to the weak implementation of the learning process in elementary schools which makes student less participation in the learning process. This research was a school action research conducted at 001 Pujud Public Elementary School and 002 Pujudti Elementary School. The subjects of this study were 12 elementary school teachers. The strategy used in this research is collaborative educational supervision. The purpose of this study was to improve teacher performance in the learning process. This research was conducted in two cycles. The results showed that the results of planning in the first cycle got a value of 72.1% and increased in the second cycle to 87.9%. The evaluation on the implementation of the first cycle scored 71.9% and increased in the second cycle to 88.6%. The evaluation on the first cycle got a score of 71.2%, and in the second cycle increased to 90.7%. The assessment of follow-up in cycle I was 64.96% and in cycle II it increased to 88.2%. It can be concluded that by implementing collaborative educative supervision can improve teacher competence in the learning process carried out in elementary schools.